Infraestructura para la monitorización del consumo energético en redes b5G/6G. - Álvarez-Merino, Carlos Simón; Segura, David; Baena, Carlos; Khatib, Emil Jatib; Barco-Moreno, Raquel (My University, 2024)
Sustainability is a critical factor in the development of future beyond-5G (b5G)/6G networks. This work highlights the importance of energy efficient practices to reduce environmental impact and resource consumption, in line with the objectives of the International Mobile Telecommunications (IMT) 2030. The increasing energy consumption in telecommunications networks highlights the need for corrective action without compromising network performance or security. The paper presents an Open Radio Access Network (O-RAN) architecture for 5G networks that enables the monitoring and optimization of energy consumption. The study integrates xApps and rApps into various emulated network elements to provide a real streaming service while monitoring the power consumption of the different network elements.
Keywords: Eficiencia energética; b5G; 6G; Monitorización; Arquitectura de red